Hadith #1915 - Sahih al-Bukhari - Abu Aiyub from Juwairiya bint Al-Harith (Sahih al-Bukhari)
The Prophet (ﷺ) visited her (Juwairiya) on a Friday and she was fasting. He asked her, “Did you fast yesterday?” She said, “No.” He said, “Do you intend to fast tomorrow?” She said, “No.” He said, “Then break your fast.” Through another series of narrators, Abu Aiyub is reported to have said, “He ordered her and she broke her fast.”
Grade: Sahih

Hadith #5755 - Sahih al-Bukhari - Abu Aiyub from Juwairiya bint Al-Harith (Sahih al-Bukhari)
A man said, “O Allah’s Messenger (ﷺ)! Inform me of a deed which will make me enter Paradise.” The people said, “What is the matter with him? What is the matter with him?” Allah’s Messenger (ﷺ) said, “He has something to ask (what he needs greatly).” The Prophet (ﷺ) said (to him), (In order to enter Paradise) you should worship Allah and join none in worship with Him: You should offer prayers perfectly, give obligatory charity (Zakat), and keep good relations with your Kith
Grade: Sahih

Hadith #5846 - Sahih al-Bukhari - Abu Aiyub from Juwairiya bint Al-Harith (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “It is not lawful for a man to desert his brother Muslim for more than three nights. (It is unlawful for them that) when they meet, one of them turns his face away from the other, and the other turns his face from the former, and the better of the two will be the one who greets the other first.”
Grade: Sahih

Hadith #6002 - Sahih al-Bukhari - Abu Aiyub from Juwairiya bint Al-Harith (Sahih al-Bukhari)
The Prophet (ﷺ) said, “It is not lawful for a Muslim to desert (not to speak to) his brother Muslim for more than three days while meeting, one turns his face to one side and the other turns his face to the other side. Lo! The better of the two is the one who starts greeting the other.”
Grade: Sahih